2013
DOI: 10.5541/ijot.449
|View full text |Cite
|
Sign up to set email alerts
|

Performance Estimation and Optimal Operation of a CO2 Heat Pump Water Heating System

Abstract: IntroductionHot water demand occupies about one-third of the energy consumption in the residential sector in Japan, and energy saving in hot water supply has been an important issue. Under this situation, water heating systems each of which is composed of a heat pump using CO 2 as a natural refrigerant and a hot water storage tank have been developed and commercialized widely (Saikawa, 2004;Hashimoto, 2006). The performance of CO 2 heat pumps has been enhanced dramatically through the technological development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Dietrich et al [6] studied the exergoeconomic performance of a pumped heat electricity storage system and they concluded that this system can be considered as a worthy solution for the storage of the electrical energy. Yokoyama et al [7] proposed a method in order to investigate the energy performance of a CO2 heat pump water heating system. Castaing-Lasvignottes et al [8] investigated a model of a compressed air energy storage system which was connected to photovoltaics panels and to the grid and their purpose was to eliminate the energy from the grid.…”
Section: Introductionmentioning
confidence: 99%
“…Dietrich et al [6] studied the exergoeconomic performance of a pumped heat electricity storage system and they concluded that this system can be considered as a worthy solution for the storage of the electrical energy. Yokoyama et al [7] proposed a method in order to investigate the energy performance of a CO2 heat pump water heating system. Castaing-Lasvignottes et al [8] investigated a model of a compressed air energy storage system which was connected to photovoltaics panels and to the grid and their purpose was to eliminate the energy from the grid.…”
Section: Introductionmentioning
confidence: 99%
“…Some review papers on the performance analysis of CO 2 enhance the performance by extracting tepid water from a storage tank [36]. In addition, operation and design optimizations have been tried: Yokoyama et al have estimated system performance values and have clarified the optimal operating conditions under daily change in simulated hot water demand [37]; Deng et al have analyzed and optimized the performance of a combination of a solar heater and an HP WHS [38]. These results have been obtained for uni-functional systems with the function only of hot water supply.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some studies have been conducted under unsteady states including charging and tapping modes: Fernandez et al have investigated the performance of a water heating system composed of a heat pump and a storage tank in the charging mode [26]; Yokoyama et al have conducted numerical simulations on such a system and have clarified the effects of the ambient and operation temperatures on system performance values under a daily cyclic change in hot water demand [27,28]; Yokoyama has conducted the exergy analysis of the system based on the results obtained by numerical simulation [29]; Yokoyama et al have also investigated daily changes in system performance values under daily changes in standardized and simulated hot water demands [30,31]. In addition, operation and design optimizations have been tried: Yokoyama et al have investigated the optimal conditions for operating temperatures under daily change in simulated hot water demand, which is based on the estimation of system performance values in place of the numerical simulation [32]; Deng et al have investigated performance analysis and optimization of a combination of a solar heater and a heat pump water heating system [33]. However, all the studies have been conducted by assuming that conventional storage tanks with outlets for hot water supply on their tops are installed.…”
Section: Introductionmentioning
confidence: 99%